A ANALISIS STATUS TINGGI BADAN PENDEK DENGAN USIA MENARCHE: LITERATURE REVIEW - Malisa Ariani; Dwiti Hikmah Sari; Anggrita Sari (LPPM Universitas Sari Mulia, 2020)
Background: The increased of the age of menarche in adolescent girls has accelerated and delayed menarche. One of the factors that influence the age of menarche is nutrition status, where adolescent girls with short height will affect the age of menarche. Objective: This study aims to analyze literature about short height status with menarche age. Method: This study used a literature study approach by using several sources selected based on criteria inclusion. Results: The review results found that short height status is related to the age of menarche. The average age of menarche is 12-14 years with the lowest age of 9 years and the highest is 15 years, while the average height of the body is 156.8 cm with the lowest of 139 cm and the highest of 168 cm. Conclusion: Adolescent girls with higher height anthropometrics oppose precarch menarche, otherwise adolescent girls with lower anthropometry will find it difficult to menarche tarda. Therefore, parents must pay attention to the basic needs to support that are covered by puberty and the arrival of menarche in normal age so that children will have more optimal growth opportunities and can reach maximum height.